The Biomechanical Effect of Bone Grafting and Bone Graft Remodeling in Patients With Anterior Shoulder Instability. Issue 8 (July 2020) - Sigrist, Bastian; Ferguson, Stephen; Boehm, Elisabeth; Jung, Christian; Scheibel, Markus; Moroder, Philipp
Background: Individual constitutional differences in glenoid shape and bone remodeling require a patient-specific and longitudinal approach to evaluate the biomechanical effects of glenoid bone grafting in patients with anterior shoulder instability. Purpose: To quantify the longitudinal, in vivo, biomechanical effects of bone grafting, bone graft remodeling, and glenoid shape in patients with anterior shoulder instability by means of patient-specific finite element models. Study Design: Descriptive laboratory study. Methods: In total, 25 shoulders of 24 patients with anterior shoulder instability and anterior glenoid bone loss underwent an arthroscopic iliac crest bone graft transfer (ICBGT) procedure with either autologous or allogenic bone. Patient-specific finite element simulations based on preoperative, postoperative, and follow-up computed tomography scans were used to quantify the bone-mediated stability ratio (SR) and the distance to dislocation. Additionally, the relationship between glenoid morphological parameters and the SR was assessed. Results: The ICBGT procedure significantly increased the SR and distance to dislocation in the 2-, 3-, and 4-o' clock directions immediately after the surgical intervention ( P < .01) in both the autograft and the allograft groups. Although the SR and distance to dislocation decreased subsequently, autografts showed long-term effects on SR and dislocation distance in the 3-o'clock direction ( P < .01) and on SR in the 4-o'clock direction ( P < .01). Allografts showed no significant effect on SR and dislocation distance in long-term follow-up ( P > .05). Overall, glenoid retroversion as well as cavity depth predicted stability in all 4 dislocation directions, with glenoid cavity depth showing the highest correlation coefficients ( R = 0.71, 0.8, 0.73, and 0.7 for 2-, 3-, 4-, and 5-o'clock, respectively). Conclusion: The autologous ICBGT procedure biomechanically improved anterior shoulder stability in long-term follow-up, whereas the use of allografts did not show any bone-mediated biomechanical effect at follow-up due to resorption. Furthermore, in addition to measurements of defect extent, the glenoid depth and version seem to be useful parameters to determine the biomechanical effect and need for glenoid bone grafting in patients with shoulder instability. Clinical Relevance: This study proposes the use of autologous bone grafts for a successful long-term stabilization effect. Additionally, this study proposes additional glenoid morphological measures to predict shoulder stability.